The Understanding of Muballigh Regarding Zakat Literacy: Empirical Evidence Based on The Zakat Literacy Index - Choirin, Muhammad; Arbi, Dion Saputra; Junaedi, Jujun; Setiawan, Asep Iwan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study emphasizes the significance of Zakat literacy in advancing da'wah, especially in Indonesia where Zakat collection falls short. The focus is on assessing the comprehension levels of Indonesian Muballigh, who are key agents of da'wah, regarding zakat as a fundamental pillar of Islam. Utilizing a mixed-methods approach, the research employs both quantitative and qualitative methods. The Zakat Literacy Index (ZLI quantitatively measures comprehension levels among 50 Indonesian Mubaligh respondents. Additionally, a comprehensive literature study is conducted for a nuanced understanding of the subject. The study reveals a robust Zakat Literacy Index score of 80.66, indicating solid basic comprehension. However, there is room for improvement in advanced understanding, rated at a moderate level. Therefore, this research measures the understanding of preachers or muballighs regarding zakat which is the main source for society to study and understand religious knowledge, especially how to fulfil the obligation of zakat as a pillar of Islam.